Changes in Customer Behavior Towards Video Advertising Post-Pandemic - Surjandy Surjandy; Cadelina Cassandra (Journal of Information Systems Engineering and Business Intelligence)
Background: Video Advertising (VI) is a powerful media tool used by several companies as a marketing strategy. During COVID-19 pandemic, there was a wide adoption of digital media, particularly VI, to promote company products. However, some changes occurred post-pandemic, which influenced customer behavior.